IMPLEMENTASI PROGRAM KAMPUS MENGAJAR BATCH 8 DALAM PENINGKATAN LITERASI SEKOLAH DASAR NEGERI - Ramdani, Faisal Tri; Suradika, Agus; Aziz Samudra, Azhari (Administratie: Jurnal Administrasi Publik, 2025)
This study assessed the results of the Implementation of the Kampus Mengajar Program batch 8 in improving literacy in Public Elementary School students in Bogor Regency. Using a mixed-method approach, quantitative data were obtained from pre-tests and post-tests of student literacy and from filling out questionnaires. In contrast, qualitative data came from interviews with teachers, principals, and student participants in the program and the results of filling out questionnaires. The results showed a significant increase in students' post-test scores by 25.4% compared to the pre-test (t = 8.76, p < 0.01). Interviews revealed that students' creative learning methods increased student motivation and participation despite obstacles such as limited facilities. The results of the accumulation of respondents' questionnaire responses were rated very good, with a score of 4.29. This program has clear objectives and a good coordination process supported by a strong community and students who are competent in running the program so that it can be well received and have good program results. This program proves its Implementation in supporting the improvement of student literacy and underlines the importance of student training before Implementation. This study recommends developing educational policies based on collaboration between universities and elementary schools and expanding Implementation in other areas.